2022
DOI: 10.3389/fimmu.2021.758829
|View full text |Cite
|
Sign up to set email alerts
|

Small Proline-Rich Protein 3 Regulates IL-33/ILC2 Axis to Promote Allergic Airway Inflammation

Abstract: Small proline-rich proteins (SPRRs), components of cornified cell envelope precursors, have recently been found to participate in airway diseases. However, their role in allergic airway inflammatory conditions remains unknown. Here, we explored the expression of SPRR3 in house dust mite (HDM)-sensitized/challenged mice and attempted to elucidate the regulatory role of SPRR3 in allergic airway inflammation. SPRR3 was identified via bioinformatics analysis of Gene Expression Omnibus (GEO) databases and further c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Accordingly, PI3Kδ reduced the expression of IL‐33 and number of ILC2s, thereby inhibiting the allergic inflammatory response 34 . Leptin, a small proline protein, and LAIR‐1 regulate ILC2s by targeting the PI3K‐AKT pathway, hence affecting the severity of asthma 35–37 . Therefore, we hypothesized that IL‐33 and ILC2s play a role in asthma via the PI3K/AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, PI3Kδ reduced the expression of IL‐33 and number of ILC2s, thereby inhibiting the allergic inflammatory response 34 . Leptin, a small proline protein, and LAIR‐1 regulate ILC2s by targeting the PI3K‐AKT pathway, hence affecting the severity of asthma 35–37 . Therefore, we hypothesized that IL‐33 and ILC2s play a role in asthma via the PI3K/AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported by Li and Sakai et al (20,21), who found that ST2, the receptor for IL-33, was not expressed by liver resident macrophages, thereby demonstrating that endogenous IL-33 exerts a hepatoprotective effect as a result of increased NF-kB and Bcl-2 expression in hepatocyte and is independent of KCs. However, results from several studies have indicated that IL-33/ILC2s regulate M2 polarization of macrophages (40)(41)(42) and that IL-33 can stimulate ILC2 proliferation (19,43,44), leading to the conclusion that although IL-33 is capable of regulating the polarization of macrophages in vivo, this ability is reliant on ILC2s. Our findings, as described above, suggest that the protective effects of ILC2s in hepatic IRI may rely on exogenous IL-33.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous IL-33 is a potent stimulator of ILC2 proliferation (19), and a role for IL-33 in mouse models of hepatic IRI has been previously described. Li Shu et al demonstrated that pretreatment with exogenous IL-33 reduced warm hepatic IRI in mice, and that this protective effect of IL-33 on hepatic IRI was mainly due to a Th1 to Th2 type shift (20).…”
Section: Introductionmentioning
confidence: 95%
“…Among them, Akt was identified as a unique signaling intermediate in bone homeostasis that controlled the differentiation of osteoblasts and osteoclasts, which was a direct downstream target of PI3K to inhibit the release of inflammatory factors [32][33][34][35][36]. Moreover, NF-κB was also a key downstream factor of the PI3K/Akt pathway, which enhanced the degree of inflammatory response and promoted the differentiation of osteoclast precursors [37,38]. Meanwhile, the PI3K/Akt signaling pathway not only affects inflammatory factors such as NF-κB and TNF-α but also induced the inflammatory reaction in the internal environment of the body.…”
Section: Discussionmentioning
confidence: 99%